Towards an Understanding of Information Technology Strategy Development Based on Knowledge Management - Paulo Henrique de Souza Bermejo; Adriano Olímpio Tonelli; Andre Luiz Zambalde; José Leomar Todesco (Revista de Ciências da Administração : RCA, 2014)
The formulation of IT strategies is increasingly seen as a collaborative process, where knowledge management (KM) and learning become central to building a shared view of how information technology (IT) can support and extend business strategies. This article presents three interrelated components that support the application of KM to IT strategy development (actors and types of knowledge, knowledge conversion modes, and technological tools and artifacts). Through a longitudinal, qualitative case study, we illustrate strategies for applying these components. Faced with the importance of knowledge and collaboration to IT strategies, the results provide recommendations so that organizations can apply concepts and practices of KM processes in formulating IT strategies.